Netflix's Digital Transformation Strategy: A Systematic Review of Challenges and Risk Mitigation Approaches - Nelsa, Putri; Paradita, Anggraeni Xena; Hermawan, Fairuz Fernanda; Ghifari, Muhamad Yazid; Lubis, Muharman (STKIP PGRI Tulungagung, 2025)
Digital transformation requires organizations to quickly adapt and keep up with technological changes and developments to remain competitive. Implementing transformation helps improve performance, efficiency, revenue, and organizational culture. However, the process is complex, difficult, and high-risk. Failure in digital transformation can be highly detrimental due to the significant investments required in terms of material and human resources. Not only do some organizations fail, but many are also able to overcome these challenges and succeed in transforming in the desired direction. One large and successful company in digital transformation is Netflix. This large streaming-based company is interesting to analyze for its achieved success. This study's purpose is to identify and analyze the strategies used by Netflix in overcoming challenges and risks during the digital transformation process. This study employs the Systematic Literature Review (SLR) method. Information was gathered from journals and articles spanning the last 4-5 years. This search used tools such as Google Scholar, Semantic Scholar, and an application called Publish Perish8, with keywords like